Democratic legitimacy [ - Peter, Fabienne (Routledge studies in social and political thought, 2009)
Offers a treatment of the requirements of democratic legitimacy. This book intends to propose a framework for distinguishing among the different ways in which the requirements of democratic legitimacy have been interpreted. It uses this framework to identify and defend what appears as the most plausible conception of democratic legitimacy